2010
DOI: 10.1111/j.1747-0285.2010.01023.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Highly Stereoselective Synthesis of Cyano Aziridines via the CuCl‐Catalyzed Aminochlorination of α,β‐Unsaturated Nitriles and Intramolecular SN2 Substitution

Abstract: An efficient one-pot system has been developed for the synthesis of cyano aziridine by using a,bunsaturated nitriles as the alkene substrates and N,N-dichloro-p-toluenesulfonamide (4-TsNCl 2 ) as the nitrogen source. A good scope of alkene substrates was achieved for this reaction. The one-pot reaction, via aminohalogenation and intramolecular S N 2 substitution, was very convenient to carry out at room temperature without the protection of inert gases. Modest to good yields and excellent have been obtained. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…values so obtained varied with substrate and sulfonimidamide, but reached 94% in one instance (Scheme 22). Han, Pan and co-workers have described a protocol for Cu-catalysed aziridination of a,b-unsaturated nitriles, using N,N-dichlorotoluenesulfonamide as nitrogen source and oxidant 99 (in contrast to their diamination protocol, 88 acetonitrile is not incorporated in this instance). Finally, Morales, Pe´rez and co-workers have employed 1,3,5-tris(thiocyanatomethyl)mesitylene as a ligand, investigating the corresponding Cu complex as a nitrene transfer agent.…”
Section: Scheme 18 Scheme 19mentioning
confidence: 99%
“…values so obtained varied with substrate and sulfonimidamide, but reached 94% in one instance (Scheme 22). Han, Pan and co-workers have described a protocol for Cu-catalysed aziridination of a,b-unsaturated nitriles, using N,N-dichlorotoluenesulfonamide as nitrogen source and oxidant 99 (in contrast to their diamination protocol, 88 acetonitrile is not incorporated in this instance). Finally, Morales, Pe´rez and co-workers have employed 1,3,5-tris(thiocyanatomethyl)mesitylene as a ligand, investigating the corresponding Cu complex as a nitrene transfer agent.…”
Section: Scheme 18 Scheme 19mentioning
confidence: 99%
“…The aminohalogenation reaction has been well studied in the past decade [2932], and the corresponding vicinal haloamine product can be easily converted into aziridines [3334] and α,β-dehydroamino acid derivatives [35] in the presence of an organic amine. Recently, we found that treating haloamine with benzylamine resulted in an unexpected α,β-diamino product, instead of the aziridine or the α,β-dehydroamino product.…”
Section: Introductionmentioning
confidence: 99%